2020
DOI: 10.1039/d0an01119c
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry-based identification of ortho-, meta- and para-isomers using infrared ion spectroscopy

Abstract: Distinguishing positional isomers presents a significant challenge for mass spectrometric analyses, for instance in drug metabolism research. We show that IR ion spectroscopy readily identifies ortho-, meta- and para-isomers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…The Cs + ion is the dominant fragmentation product formed and is well above the low-mass cut-off of the mass spectrometer (in contrast, Na + and K + are below the low-mass cut-off) and thus can be included in IRMPD yield calculations. The use of IRMPD yield instead of depletion of the precursor intensity can significantly improve the signal-to-noise ratio by accounting for fluctuations in total ion intensity during electrospray. , The Cs + tag likely has some influence on the conformation and IRMPD spectrum; however, Cs + has been shown to have less of an impact in comparison to other adducts such as Na + due to its much larger ionic radius, more diffuse charge, and much weaker binding energy. ,,, Once the lowest-energy conformers are determined, DFT calculations with and without the Cs + ion can provide insights into the overall effect of this weakly bound ion on the gas-phase conformation. ,,, Finally, as noted above, the absolute intensity of the spectral bands is higher in the Cs + spectrum due to the decreased dissociation energy.…”
Section: Resultsmentioning
confidence: 99%
“…The Cs + ion is the dominant fragmentation product formed and is well above the low-mass cut-off of the mass spectrometer (in contrast, Na + and K + are below the low-mass cut-off) and thus can be included in IRMPD yield calculations. The use of IRMPD yield instead of depletion of the precursor intensity can significantly improve the signal-to-noise ratio by accounting for fluctuations in total ion intensity during electrospray. , The Cs + tag likely has some influence on the conformation and IRMPD spectrum; however, Cs + has been shown to have less of an impact in comparison to other adducts such as Na + due to its much larger ionic radius, more diffuse charge, and much weaker binding energy. ,,, Once the lowest-energy conformers are determined, DFT calculations with and without the Cs + ion can provide insights into the overall effect of this weakly bound ion on the gas-phase conformation. ,,, Finally, as noted above, the absolute intensity of the spectral bands is higher in the Cs + spectrum due to the decreased dissociation energy.…”
Section: Resultsmentioning
confidence: 99%
“…This may imply that the case sample contains a mixture of MW 167 isomers. With this hypothesis in mind and careful inspection of the spectra in Figure , one may estimate which of the isomers are actually present, especially from the 650–900 cm –1 region where ortho-, meta-, and para-isomers have distinct spectral signatures, originating from the out-of-plane CH-bending vibrations of the aromatic ring. , This suggests that 2-FMA (ortho) and 4-FMA (para) are present in the case sample.…”
Section: Resultsmentioning
confidence: 99%
“…Vibrational resonances are highly sensitive to details of the molecular structure, such that closely related isomeric molecular ions can often be differentiated on the basis of their IR spectra. Indeed, a range of studies have shown that IRIS can distinguish isomeric small molecules [16][17][18][19][20][21][22][23][24][25][26][27][28] , including several phase-I drug metabolites [29][30][31] . A significant advantage in comparison to techniques based on MS/MS fragmentation patterns is that gas-phase IR spectra can be reliably and efficiently predicted using quantum-chemical calculations based on density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…18,32 Previous work has demonstrated IRIS-based differentiation of ortho-, meta-and para-isomers that may result from the hydroxylation of drug compounds containing a phenyl moiety. 29,31 In one of these studies, metabolites were extracted and analyzed from an in vitro drug incubation sample using a combination of LC-MS and IRIS. 29 However, a drug molecule often undergoes several phase I (oxidation, hydrolysis or reduction) and phase II (conjugation) biotransformation reactions that occur sequentially.…”
Section: Introductionmentioning
confidence: 99%